PERBEDAAN LAMA WAKTU MOULTING KEPITING BAKAU (SCYLLA SERRATA) JANTAN DENGAN METODE MUTILASI DAN ABLASI - WILDAN HABIBI, M. (Universitas Negeri Surabaya, 2013)
Mud crabs from a natural catchment have a high economic value. From some of the natural catchments, there are soft shell crabs with relatively long moulting periods, about 2 – 3 months. Soft shell crab needs always increase. So, an intensive cultivation is necessary to produce moulting crabs. The purpose of this research was to identify the influence of walking legs mutilations and eyes stalks ablation to the male mud crab moulting periods. This research used experimental research type and completely randomized design (RAL) with three replications. The treatments consisted of mutilation of a pair of the first walking legs, a pair of the second walking legs, a pair of the third walking legs, a pair of claws, a pair of claws and all walking legs, and eyes talk ablation. Crabs used was mud crabs with hard carapaces. The test parameter was moulting period of mud crabs measured from the crabs still had hard carapaces until their moulting were complete. Data obtained in the form of moulting period of mud crabs using mutilation and ablation methods and control mud crabs were analyzed descriptive quantitatively. The results indicated that the methods of mutilation and ablation can accelerate mud crab moulting periods. Mutilation of a pair of claw and all walking legs is the treatment that produces the best moulting time compared with others with their moulting duration are 17-23 days.   Key words: mutilation; ablation; mud crab; moulting period; moulting